An experimental investigation of liquid immersion cooling of a four cell lithium-ion battery module - O'Shaughnessy, Seamus; Trimble, Daniel (My University, 2024)
The thermal management of a lithium-ion battery module subjected to direct contact liquid immersion cooling conditions is experimentally investigated in this study. Four 2.5 Ah 26650 LiFePO4 cylindrical cells in a square arrangement and connected electrically in parallel are completely immersed in the dielectric fluid Novec 7000. The thermal and electrical behaviour of the module is assessed at charging and discharging rates of 1C to 4C. Experiments are conducted with initially ambient temperature liquid, resulting in single phase natural convec- tion cooling, as well as preheated liquid temperatures of 33 ◦C ± 0.5 ◦C to study the influence of the phase change process under pool boiling conditions. Superior performance is observed when two-phase immersion cooling conditions are established for discharge rates of 2C and above, limiting the average cell temperature rise to 1.9 ◦C at the end of 4C discharge, corresponding to a maximum temperature of 34.7 ◦ C. For the most onerous charging rate of 4C, considered fast charging, this maximum temperature rise is limited to 1.3 ◦C, corresponding to a maximum temperature of 35 ◦C. Vigorous boiling is observed from the cells’ electrodes, leading to more effective heat transfer from the locations of high heat flux. Excellent module thermal homogeneity is exhibited, maintaining a maximum temperature difference of 1.2 ◦C for all cases investigated. The axial temperature gradients of the module’s individual cells are also greatly reduced under two-phase conditions. The influence of cell spacing within the module is also investigated for inter-cell spacings of 0.25D and 1D, where D is the cell diameter. Marginally improved heat transfer performance is observed for the more closely spaced cell ar- rangements, reducing the maximum cell temperatures and thermal inhomogeneity within the module.
PUBLISHED
Keywords: Immersion cooling; Two-phase cooling; Electric vehicles; Fast charging; Dielectric liquid; Battery thermal management